High-Throughput Native Mass Spectrometry Screening in Drug Discovery - Gavriilidou, Agni F. M.; Sokratous, Kleitos; Yen, Hsin-Yung; De Colibus, Luigi (Frontiers in Molecular Biosciences, 2022)
The design of new therapeutic molecules can be significantly informed by studying compound interactions directly to the target protein, following their purification, using biophysical approaches. Well-established techniques utilized in drug discovery include isothermal titration calorimetry, surface plasmon resonance, nuclear magnetic resonance spectroscopy, and structure-based drug discovery (SBDD) techniques, which mainly relies on protein crystallography and, more recently, cryo-electron microscopy. Protein-ligand complexes are dynamic, heterogeneous, and challenging systems to study only with one technique. Native mass spectrometry (MS) is a versatile method used to study proteins and their non-covalently driven assemblies at a native-like folded state, providing information on binding thermodynamics and stoichiometry as well as insights on protein’s ternary and quaternary structures. Here, we discuss the basic principles of native MS, the field's recent progress, how it is integrated into a drug discovery pipeline, and what improvements can be made.